Systemic lupus erythematosus diagnosed during pregnancy: a case report - Coelho Junior, Luilson Geraldo; Machado, Gabrielly Borges; Figueiredo, Estevão Tavares de; Faria, Talitha Araújo (Revista de Medicina, 2015)
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease of autoimmune etiology, multisystem distribution, whose clinical manifestations are quite variable. Genetic and environmental factors are correlated with the development of the disease, which is characterized by periods of remission and exacerbation. In SLE, immunological phenomena lead to the production of auto-antibodies, which are directed to nuclear antigens of the organism itself, resulting in different clinical manifestations and may involve the bones, joints, lungs, liver, kidneys and central nervous system. Women of childbearing age have high prevalence, and, in most cases, do not have a compromised fertility. The onset during pregnancy is rare and indicates poor prognosis for mother and fetus. Pregnancy is not recommended when the disease is active at conception. Women with lupus have high-risk pregnancy, because pregnant women lupus has high rates of abortion, intrauterine and fetal growth restriction, preeclampsia, fetal death, preterm delivery. There is controversy about the effect of pregnancy on disease activity, since SLE can affect pregnancy, and the reverse can also occur; however, the SLE should not be understood as a limitation to pregnancy, and the monitoring thereof should be done by multi-professional team, ensuring a safe pregnancy for mother and fetus. We present the case of a patient diagnosed with SLE in the first trimester of pregnancy and that presented clinical and laboratory evolution rapid and unfavourable, evolving with lupus nephritis and abortion.